Severe Exertional Dyspnea in a Patient with Localized Emphysema - Giuseppe Giustino; Katherine A Webb; Kenneth B Sutherland; Denis E O’Donnell (Canadian Respiratory Journal)
The case of a middle-aged, male smoker who presented with progressive severe dyspnea is described. The cause of the progressive severe dyspnea remained unexplained after a comprehensive history, physical examination, chest radiograph, electrocardiogram and spirometry. Subsequent investigations resulted in a diagnosis of localized pulmonary emphysema. Detailed exercise testing helped uncover the physiological basis of the patient’s extreme dyspnea.